Agro-Residues: Surface Treatment and Characterization of Date Palm Tree Fiber as Composite Reinforcement. (23rd November 2014) - Elbadry, Elsayed A.
Abstract : The aims of this research are to investigate the effect of different surface treatment methods on the different properties of date palm fiber (DPF) compared to raw DPF fibers such as surface morphology, density, thermal stability, and tensile properties. The first surface treatment is called surface hand cleaning which can be carried out by cleaning the fibers by soft sand cloth; the second one is the same as the first one after DPF heat treatment in the furnace at 100°C for 1.5 h and the third one is by chemical treatment with 1% NaOH at 100°C for 1 h. The results showed that the mechanical performance of DPF was enhanced by the different treatments and the chemical treatment has pronounced effect on the behavior of DPF. Raw fibers showed the highest variability and presented the lowest value of Weibull modulus, whereas the fibers showed less variability by carrying out the different treatments. Moreover, using soda treatment cleans the fiber surface which causes fibrillation and therefore the tensile strength of the fibers increases.